Multimodal Analysis of South Korean Male Skincare Advertisements - Ahmad Bakri Alhadi; Wawan Gunawan; Yanty Wirza; syihabuddin syihabuddin (Journal of English Language Studies, 2022)
The complexity of advertisements meanings realized by selected images and words always leads to multiple interpretations. This study attempts to examine the meaning representation in the Korean skincare advertisements intended for males. This study follows Kress and van Leeuwen’s (1996; 2006) systemic functional approach to multimodal discourse analysis to reveal the representational meanings from the advertisements. The data sources were three Korean skincare advertisements namely “UL.OS”, “Dandyguy”, and “Power Perfection BB Cream” selected to instantiate how verbal and visual data deliver representational meanings. Following SFL -Multimodal discourse analysis, this study focused on identifying ideational meanings of the intermodal relations in terms of their representation, interaction, and composition.  The findings showed that the intermodal relations of the Korean male skincare advertisements relied on the meanings conveyed by the elected images. The images presented a typical masculinity showing the Korean cultural identities. The meanings were complemented through the choices of verbal, material, and circumstance. This study suggests that the advertisements represent cultural identity being constructed by the choice of visual images.